Potential Value of TNF-α (–376 G/A) Polymorphism and Cystatin C (CysC) in the Diagnosis of Sepsis Associated Acute Kidney Injury (S-AK I) and Prediction of Mortality in Critically Ill patients - Al-Amodi, Hiba S; Abdelsattar, Shimaa; Kasemy, Zeinab A.; Bedair, Hanan M.; Elbarbary, Hany S.; Kamel, Hala F. M. (Frontiers in Molecular Biosciences, 2021)
Sepsis Associated Kidney Injury represents a major health concern as being frequently associated with increased risk of mortality and morbidity. Our aim was to evaluate the potential value of TNF-α (–376 G/A) and cystatin C in diagnosis of S-AKI and prediction of mortality in critically ill patients. This study included 200 critically ill patients and 200 healthy controls. Patients were categorized into 116 with acute septic shock and 84 with sepsis, from which 142 (71%) developed S-AKI. Genotyping of TNF-α (–376 G/A) was performed by RT-PCR and serum CysC was assessed by ELISA. Our results showed a highly significant difference in genotypes’ frequencies of TNF-α (–376 G/A) SNP between S-AKI and non-AKI patients (p<0.001). Additionally, sCysC levels were significantly higher in the S-AKI group (p=0.011). Combination of both sCysC and TNF-α (–376 G/A) together had better diagnostic ability for S-AKI than sCysC alone (AUC =0.610, 0.838 respectively). Both GA and AA genotypes were independent predictors of S-AKI, (p= <0.001, p=0.002 respectively). Additionally, sCysC was significantly associated with the risk of S-AKI development (OR= 1.111). Both genotypes and sCysC were significant predictors of non-survival (p <0.001). Suggesting their potential role in early diagnosis of S-AKI and prediction of mortality.